Tingkat Motivasi Belajar Mahasiswa Rantau pada Perguruan Tinggi Agama Islam Negeri di Kepulauan Riau - Dwi Rio Sudarroji; Nadya Nela Rosa (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The purpose of this study was to measure the level of learning motivation of out-of-town students at State Islamic Universities in the Kepulauan Riau. The approach used in this study is a quantitative descriptive approach. The data collection instrument used in this study was a learning motivation questionnaire. The selection of research samples was carried out by purposive sampling. The data analysis technique in this study used descriptive statistics. Based on the results obtained from the study, an overview of the level of learning motivation of out-of-town students studying at State Islamic Universities in the Kepulauan Riau has a good level of learning motivation, this is evidenced by the 131 subjects in this study being in the moderate category of 18 students and in the high category of 113 students.